Analysis of Railway Station Development Potential in Madura with Railway Reactivation - Ahmad Soimun; A.A Bagus Oka Krisna; Nengah Widiangga Gautama; Putu Ayu Govika Krisna Dewi; Annisa Mahadita Candrarahayu (Jurnal Teknologi Transportasi dan Logistik, 2022)
The reactive plan of the Madura railway line received a favorable response from four regents in Madura. As the plan can improve economic development and facilitate human and goods movements easily. In its development, the potential for the development of the island of Madura needs to be noticed in terms of both the economy and its infrastructure. The potential for development on the island of Madura itself is still impressed as not well developed compared to the city of Surabaya which is directly adjacent to the island of Madura. Notable in economic development is a condition of accessibility and support and complementary facilities such as the existing transport on the island of Madura. The purpose of this study is to analyze the potential for the development of a railway station in Madura by reactivating the railroad. the method used is a qualitative approach with a descriptive analysis method by conducting interviews/questionnaires to the Madurese community, regulators and transportation practitioner experts. Based on the results of the analysis of the existing Madura train stations, it can be concluded that there are 7 major stations with potential for station development in Madura. The potential for the development of a railway station can increase economic, tourism and industrial value. In the development of the station area, it is also necessary to pay attention to supporting facilities and tie them well with various sectors such as tourist sites, industrial locations and trade locations.